Professional competencies in digital profiles: search engine optimizers - Escandell-Poveda, Raquel (2023)
Improving employability is one of the key objectives of universities, for which it is essential to identify the competences of the professional profiles that have emerged in the digital era, such as the SEO (Search Engine Optimiser). This article proposes a competency profile and compares the degree of importance given by companies and professionals to a previously identified set of competencies. A sequential exploratory design (Dexplos) has been followed, in its derivative modality, which combines a mixed methodology by stages. The starting point was the labour demand analysis on SEO and 23 interviews were conducted with experts. From this phase, the competences are extracted and a quantitative instrument is created, which is launched as a survey to two populations: businesses and people working in SEO. The survey obtained 340 responses from businesses and 311 from professionals. Descriptive statistics are applied and the degrees of importance are compared using the T-test for differences of means for independent samples. The results show that, in addition to demanding a combination of specific communication, marketing and technology skills, a lot of importance is attached to generic skills, especially the ability to keep up to date. Professionals give more weight to all of them to the point of showing significant differences with the company in most of the competences; but similarities are observed in the ranking of relevance, which leads to a valid proposal for creating a training offer that responds to the needs of the digital society.